EMPOWERMENT AND UTILIZATION OF PLASTIC WASTE INTO HYDROPONIC MEDIA IN JEGU VILLAGE, PENEBEL DISTRICT, TABANAN REGENCY, BALI - Oktama Setyawan, I Kadek; Praditya Maha Wiguna, I Made; Dewi Puspita Ningrat, Qorry; Hari Putri, Tasya Prajna Pratisthita; Wahyudi Oktavia Gama, Adie; Lestara Permana, Gusi Putu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The COVID-19 pandemic has greatly affected people's living conditions, namely in the food sector. Therefore, to overcome these problems by applying the use of plastic bottle waste in hydroponic media. In this activity, it is expected to be able to meet food needs while at the same time overcoming the problem of plastic waste in the Jegu Village community. The method in applying the use of plastic bottle waste into hydroponic media is by socializing and applying it directly at the Jegu Village Office and carried out by evaluation with discussion. The purpose of this community service is to provide knowledge about hydroponic media and the use of existing plastic bottle waste to the people of Jegu Village. In our opinion, Jegu Village is suitable for using a farming system with hydroponic media because it has a small area of land. This community service activity hopes to increase the knowledge of the Jegu Village community in utilizing plastic bottle waste in hydroponic media.